Coordination and methodological innovation of the drawing activities of the degree in Architecture: Revisión del submódulo de dibujo del Grado en Fundamentos de la Arquitectura como adaptación al Espacio Europeo de Educación Superior - De Souza Sánchez, Pablo Miguel; Ferrer Román, Esther; Naranjo Henríquez, Iballa (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Through theoretical research and fieldwork about the adaptation of the architecture degree to the EHEA, and to be able to effectively and gradually deploy skills from the drawing submodule, the results of the coordination between subjects and a critical and comparative selection of learning activities are presented. This work also investigates the asymmetric distribution of the drawing subjects of the adaptation to the bologna plan, concluding with a proposal for independent and improved deployment of the submodule unlinked to the subjects that are not related to it.